The Legal Status of Digital Assets as Inheritance Objects from the Perspective of Islamic Inheritance Law - Jibran Hafidz (Islamic Family Law Study Program, Sharia Faculty, Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2026)
The development of digital technology has transformed the concept of property ownership, including the emergence of digital assets such as cryptocurrency, NFTs, electronic wallets, and digital accounts with economic value. This phenomenon raises legal issues in Islamic inheritance law, particularly regarding whether digital assets can be classified as objects of inheritance. This study aims to analyze the legality of digital assets as objects of inheritance from the perspective of Islamic inheritance law. The method used in this study is library research with a conceptual approach through an examination of legal doctrines, principles of Islamic inheritance, and contemporary literature on digital assets. The findings indicate that digital assets may be positioned as objects of inheritance if they fulfill the elements of al-māl, namely having economic value, being lawfully owned, being beneficial, being transferable, and not contradicting sharia principles. Digital assets may also fall within the category of tirkah if their ownership, value, and access can be clearly proven. However, certain types of digital assets, particularly cryptocurrency, require careful assessment because they are highly volatile and may potentially contain elements of gharar, dharar, and qimar. Therefore, the legality of digital assets as objects of inheritance is not absolute, but depends on the validity of ownership, the clarity of the object, lawful benefit, and the possibility of technical access by the heirs.